2022
DOI: 10.3389/fonc.2022.979154
|View full text |Cite
|
Sign up to set email alerts
|

Tumor acidity: From hallmark of cancer to target of treatment

Abstract: Tumor acidity is one of the cancer hallmarks and is associated with metabolic reprogramming and the use of glycolysis, which results in a high intracellular lactic acid concentration. Cancer cells avoid acid stress major by the activation and expression of proton and lactate transporters and exchangers and have an inverted pH gradient (extracellular and intracellular pHs are acid and alkaline, respectively). The shift in the tumor acid–base balance promotes proliferation, apoptosis avoidance, invasiveness, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 154 publications
1
34
0
Order By: Relevance
“…20 In particular, it has been demonstrated that extracellular acidity reduces the efficacy of weak base chemotherapeutics, such as doxorubicin, mitoxantrone, paclitaxel, vinblastine, and vincristine. 23 Ionization of the extracellular space renders weak base chemotherapeutics, a predominant class of cancer treatment drugs, less capable of permeating through cell membranes due to the protonation of drug. 24−26 This phenomenon is termed "ion trapping" and is responsible for the suppression of drug cytotoxicity, leading to a drug-resistant cancer cell phenotype.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In particular, it has been demonstrated that extracellular acidity reduces the efficacy of weak base chemotherapeutics, such as doxorubicin, mitoxantrone, paclitaxel, vinblastine, and vincristine. 23 Ionization of the extracellular space renders weak base chemotherapeutics, a predominant class of cancer treatment drugs, less capable of permeating through cell membranes due to the protonation of drug. 24−26 This phenomenon is termed "ion trapping" and is responsible for the suppression of drug cytotoxicity, leading to a drug-resistant cancer cell phenotype.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The body’s inherent bicarbonate pH buffering systems, which interact with acids to produce pH-neutral CO 2 and H 2 O molecules, are overridden by lactic acid production. , A consequence of acid accumulation is low extracellular pH (pH ≈ 6.5–6.8), which is recognized as a hallmark of cancer progression. , The acidity of the tumor microenvironment produces a natural selection of cellular mutations favoring the most aggressive phenotypes. Cancer cells that proliferate in the low-pH environment express increased invasion, metastasis, immune evasion, and chemoresistance. Cancer therapies, including chemotherapeutics, are negatively affected by the acidic extracellular pH through reduced drug uptake, increased drug efflux from cancer cells, or altered drug metabolism . In particular, it has been demonstrated that extracellular acidity reduces the efficacy of weak base chemotherapeutics, such as doxorubicin, mitoxantrone, paclitaxel, vinblastine, and vincristine . Ionization of the extracellular space renders weak base chemotherapeutics, a predominant class of cancer treatment drugs, less capable of permeating through cell membranes due to the protonation of drug. This phenomenon is termed “ion trapping” and is responsible for the suppression of drug cytotoxicity, leading to a drug-resistant cancer cell phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Metabonomic results indicated that STA treatment decreased the production of D-glucose, lactate, L-alanine, L-proline, and serine. Both lactate and serine have been reported to be associated with the development and exacerbation of tumors ( Woo et al, 2016 ; Bogdanov et al, 2022 ). Herein, these differential metabolites were mainly enriched in fructose and pentose phosphate metabolism and glycolysis/gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(Nagy et al, 1998;Odegaard et al, 2007) On the other hand, cleavage of PPAR-γ by caspase 1 allows its binding to the mitochondrial protein medium-chain acyl-CoA dehydrogenase (MCAD) resulting in reduced FAO and increased production of lactate, indicative of glycolytic activity. (Niu et al, 2017;Wu et al, 2020;Bogdanov et al, 2022) LXR, a nuclear receptor involved in cholesterol regulation, was suggested to contribute to the phenotype of TREM2 + macrophages in HCC. (Zhou et al, 2022) Interestingly, the transcriptomic profile of TREM2 + macrophages in NASH liver closely resembles TREM2 + TAMs found in HCC, in both patients and mouse models.…”
Section: The Tumor Microenvironment Influences Macrophage Functionsmentioning
confidence: 99%
“…Tumor cells actively contribute to generating an acidic microenvironment by aerobic glycolysis, notably through the generation of lactate. (Hanahan and Weinberg, 2011;Bogdanov et al, 2022) This acidic environment induces the immunosuppressive protein cyclic AMP element modulator (CREM) and enables binding of the myeloid-derived acidic pH selective V-domain immunoglobulin suppressor of T cell activation (VISTA) to its receptor on T cells, suppressing cytotoxicity. (Sawka-Verhelle et al, 2004;Lines et al, 2014;Johnston et al, 2019) In addition, aerobic glycolysis reduces glucose availability for macrophages, thus limiting one of the metabolic pathways leading to the generation of reactive oxygen species (ROS) and the release of inflammatory cytokines.…”
Section: The Hypoxic and Acidic Tumor Environmentmentioning
confidence: 99%